Signal Jammer - S., Seshireddy; Shanthi, (International Journal of Psychosocial Rehabilitation, 2020)
A cell phone signal jammer is a device that blocks the transmission of signals between a cell phone and a base station. In the cell phone signal jammer, we use the frequency as a mobile handset. The cell phone signal jammer creates a strong interference between the communication between the caller and receiver. This effect blocks the transmission of the signals from the networks, including UMTS, CDMA, 3G, 4G, 4G+5G, GSM, and PHS.